Preparing Chemistry Education Research Manuscripts for Publication - Taber, K.; Towns, M.; Treagust, David (ACS Publications, 2014)
This chapter offers an overview of the process of publishing reports of research in chemistry education. The chapter considers both issues of what makes a submission suitable for publication in a research journal and practical issues of what authors need to do, and what they should expect, at different stages of the process.